Prevalence and consequences of verbal aggression among bank workers: A survey into an Italian banking institution - Daniela Acquadro Maran; Antonella Varetto; Cristina Civilotti; Nicola Magnavita (Administrative Sciences, 2022)
Robberies and other violent acts by strangers and intruders are common in banks, which can lead to post-traumatic stress disorder in employees. However, the literature indicates that more subtle and less measurable forms of violence, such as psychological violence, can also cause discomfort among employees. The aim of the present work is to investigate the prevalence of verbal aggression and its consequences among 311 Italian bank employees. A self-administered questionnaire was completed by 197 employees. The results showed a high prevalence of verbal aggression in the sample. It is important to investigate and find the causes and effects of verbal aggression in order to understand the phenomenon in this workplace. Cases of verbal aggression need to be prevented and responded to appropriately. In addition, it should be noted that the effects of verbal aggression do not only affect the victim, but also the workplace, as productivity decreases, and the feeling of a safe environment is missing.
Keywords: 350; bank employees; verbal aggression; workplace violence